Iterative bidirectional decision feedback equalizer - Junhui Zhao; Wei Yang; Dongming Wang (2009 IEEE International Conference on Communication Technology and Applications, 2009)
In this paper, we propose a novel iterative approach to bidirectional decision feedback equalization (Bi-DFE). Bi-DFE performs two equalizations, one on the received signal and another on its time-reversed version. The arbitration for the forward and reverse DFEs is decided by minimum path metric in bidirectional Viterbi decoder. In order to further improve the performance of the Bi-DFE, iterative process can also be explored. The results of simulation and analysis show that the performance of the proposed iterative Bi-DFE is better than that of conventional DFE receiver such as normal mode DFE, time-reversal mode DFE, linear-combining bidirectional DFE (LC-BiDFE).